2023
DOI: 10.1038/s41598-023-27982-w
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic injections of autologous endometrial cells and platelet-rich plasma in patients with thin endometrium: a pilot randomized study

Abstract: The aim of this study was to evaluate the efficacy of hysteroscopically controlled injections of autologous platelet-rich plasma (PRP) and autologous endometrial cells as a treatment for infertile women with thin endometrium. The study enrolled 115 patients with thin endometrium (< 7 mm at implantation window) and infertility, who were divided into groups: Group 1 (the control) underwent conservative therapy; Group 2 received intraendometrial PRP injections instead of the conservative therapy; Group 3 recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Additionally, we did not analyze the platelet concentration or the content of cytokines and growth factors in the PRP. The smaller amount of PRP used for hysteroscopic injection in our study compared to the previous published study [9] may also affect the effectiveness of PRP therapy.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Additionally, we did not analyze the platelet concentration or the content of cytokines and growth factors in the PRP. The smaller amount of PRP used for hysteroscopic injection in our study compared to the previous published study [9] may also affect the effectiveness of PRP therapy.…”
Section: Discussionmentioning
confidence: 61%
“…The injected CD133+ BMDSCs were detected in the endometrium, confirming the engraftment of stem cells around the endometrial vessels and the proliferation of surrounding cells [43]. A pilot randomized study published in 2023 demonstrated the efficacy of hysteroscopic injection of autologous PRP for patients with refractory thin EM, and the curative effects of PRP may be related to the growth factors in PRP, stimulating the EM stem cells [9,44]. In the current study, 38 patients received the hysteroscopic injection and 21 patients (55.3%) exhibited an EM thickness exceeding 7 mm (with an average of 8.7 mm).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…PRP intrauterine infusions could possibly help with endometrial receptivity and studies have started to study this with encouraging results [ 4 , 37 , 38 ]. It is hypothesised that the endometrial stem cells are stimulated by the regenerative properties of PRP and improve endometrial response and embryo implantation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%